Feasibility Study Wear Rate Measurement Using 3D Scan Imaging - Kurniawan Kurniawan; Rochim Suratman; Bagus Budiwantoro; Satryo S. Brodjonegoro; Riona I. Media (Institut Teknologi Sepuluh Nopember, 2019)
This paper studied on optimizing the 3D scan parameters of flared chisel bucket teeth as a worn component to achieve prospect scanning micro wear in different percentage of volume loss. Taguchi L8 orthogonal array was used to design of experiment. Specimen composed in three different volume loss 1%, 3%, and 5% were scanned to obtain model CAD volumes. Volume dissimilarity was calculated by comparing model CAD volume and mass – density conversion. Shutter Time, grid, distance, and meshing were chosen as 3D scan parameters. Biggest effect and optimal scanning parameter were determined using the signal-to-noise (S/N) ratio which was calculated for volume dissimilarity according to the ‘‘the-smaller-the-better’’ approach. The effects of scanning parameter were evaluated by analysis of variance. 3D imaging feasibility study for small volume measurement could be a critical point in micro wear measurement. The statistical analysis indicated that the parameters that have the biggest effect on volume dissimilarity with 1%, 3%, and 5% volume loss are the meshing method and distance, respectively. The optimal setting parameter capturing image is 12 ms shutter time with normal meshing above 15 mm distance. Additionally, the interaction scanning parameter for 1%, 3%, and 5% volume loss was presented.